Healthy aging of the left ventricle in relationship to cardiovascular risk factors: The Multi-Ethnic Study of Atherosclerosis (MESA). - Chia-Ying Liu; Shenghan Lai; Nadine Kawel-Boehm; Harjit Chahal; Bharath Ambale-Venkatesh; Joao A C Lima; David A Bluemke (PLoS ONE)
Background Understanding the relationship of cardiovascular structure and function to age is confounded by the high prevalence of traditional risk factors in the United States. The purpose of the study is to compare left ventricular (LV) and aortic structural, and functional parameters in individuals with and without traditional risk factors in a population-based cohort. Methods and results 3015 study participants (48% men, age 55-94, mean 69.01±9.17 years) in the Multi-Ethnic Study of Atherosclerosis (MESA) underwent cardiovascular magnetic resonance (CMR) imaging from 2010-2012. Absence of cardiovascular (CV) risk factors (no hypertension, diabetes or impaired fasting glucose, obesity, smoking or hypercholesterolemia) was infrequent, occurring in just 314 (10.4%, 38% men) of 3015 participants. In multivariable analyses adjusting for age, sex and race, individuals with CV risk factors had significantly larger LV mass index (by 17%) and lower LV contractibility (circumference strain, lower by 14%). Indexed LV volumes and stroke volume were inversely associated with age, but such relationships were not statistically significant in risk-free male subjects (p>0.05). Men with CV risk factors showed positive association of CMR T1 indices of myocardial fibrosis with age. Aortic function was similar in individuals with and without risk factors; age was associated with decline of aortic function in both CV and no CV risk factor groups. Conclusion Our results support that LV structure and function are better preserved in senescent hearts in the absence of traditional cardiovascular risk factors, and such protection is more prominent in men than in women.